TOO LITTLE, TOO LATE: FROM THE CHILEAN WINTER TO THE LATIN AMERICAN SPRING. - Rice, Roberta (Journal of International Affairs, 2020)
The 2011 global protest cycle, which included the Arab Spring uprising against authoritarian rule, the Chilean Winter protests to end forprofit education, and the Occupy Wall Street movement in the United States to highlight income inequality, marked the most important protest cycle since the movements of the 1960s in Europe and North America. Protest cycles are critical opportunities to effect political and institutional change, yet progress is not guaranteed. The key factors for fostering a positive link between protest levels and long-term reform are the permeability of political institutions to protesters’ demands and the willingness of demonstrators to engage with those institutions. The central argument of this piece is that the 2011 Chilean Winter protesters asked for too little, and by doing so, missed their historic opportunity to bring about fundamental change. Instead of demanding structural change to the political and economic models underpinning their system of governance, they asked for policy change within that system. By 2019, when Chilean protesters demanded constitutional reform, their window of opportunity for deep-seated political and institutional change had already closed.